Pengukuran Getaran Untuk Menentukan Tingkat Kerusakan Pada Sistem Transmisi Variable Speed Mesin Milling Dengan Menggunakan Getaran Overall - ariyanto ariyanto (Manutech : Jurnal Teknologi Manufaktur, 2019)
Vibration measurement on moving machine components is useful to determine the feasibility of an engine. Measurements can be made using simple tools and the five senses or by using measuring devices. The results of vibration measurements are compared using standard comparisons or referring to similar machines. Measurement of vibration of knee type milling machine transmission system that has a variable speed transmission system is done by using the overall vibration value using a transducer which is placed in the radial and axial position. Measurements are taken on a variable speed system that is not indicated to have been damaged and on an engine that is indicated to have experienced damage. On machines that are not indicated to have damage, the overall axial direction is 0.363 mm / s rms and radial direction is 0.365 mm / s rms, compared to the ISO 2372 standard, the transmission system enters the area well. Measurements on the transmission system that experienced damage to the transmission shaft rotation 862 rpm axial direction has a vibration value of 4.5mm / s rms radial direction 3.47 mm / s rms, on the transmission shaft rotation 762 rpm axial direction 3.28 mm / s rms radial direction 1.68 mm / s rms, at 669 rpm axial direction 2.92mm / s rms on the transmission shaft, radial direction 1.32mm / s rms. From the measurement results on the transmission system which indicated damage, the overall vibration value at the axial rotation of the 862 rpm axial direction system is no longer eligible for operation, because based on the ISO 2372 vibration standard the vibration value has entered the area of ?? damage occurs.